Situación socioeconómica y desarrollo familiar de los comerciantes informales en el contexto inmediato del mercado central de Machala año 2019 - Pérez Salazar, Erick Andrés; Robayo Flores, Alexandra Paola (Machala : Universidad Técnica de Machala, 2019)
This research addresses the "socioeconomic situation and family development of informal traders in the immediate context of the central market of Machala, year 2019", within the framework of a city that presents divergent aspects between urban regeneration with an image of order and formality in the various aspects, both of cobbled streets, silver railings, signage and commerce, in front of the interface of areas where the momentary appropriation of public space has become the scene of the exchange of goods and services, in a symbiosis of the informality that provides a medieval aspect but that is justified in the need for subsistence, which due to improvisation many are the people who are excluded from the sources of employment in the large production units, the street is the resource where lavish initiatives on how to obtain material resources that allow them to finance food costs action, clothing, housing, education and health of the members of their families. In Machala, informal trade is not only expressed in the form of coexistence of a city environment combined by ruralist descent, but also has cultural and structural characteristics.
La presente investigación aborda la “situación socioeconómica y desarrollo familiar de los comerciantes informales del contexto inmediato del mercado central de Machala, año 2019”, en el marco de una ciudad que presenta aspectos divergentes entre la regeneración urbana con una imagen de orden y formalidad en los diversos aspectos, tanto de las acalles adoquinadas, de los pasamanos plateados, la señalética y del comercio, frente a la interfaz de áreas donde la apropiación momentánea del espacio público se ha convertido en el escenario del intercambio de bienes y servicios, en una simbiosis de la informalidad que brinda un aspecto medieval pero que se justifica en la necesidad de la subsistencia, que a la fuerza de la improvisación muchas son las personas que excluidas de las fuentes de empleo en las grandes unidades de producción, la calle es el recurso donde prodigarse las iniciativas de cómo obtener recursos materiales que les permitan financiar los costos de alimentación, vestido, vivienda, educación y salud de los integrantes de sus núcleos familiares.
Keywords: SOCIOECONOMICA; COMERCIANTE; DESARROLLO; MERCADO